Application of Modern Technologies in the Storage and Processing of Food Grapes - Davronov Qaxramonjon Anvarjonovich; M.Yoldasheva (Genius Journals, 2022)
This article talks about the importance of innovative technologies in the development of viticulture in our country, as well as in the preservation and processing of cultivated grape varieties.
Keywords: Innovative Technologies; Viticulture; Grape Varieties